ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PEMILIHAN JURUSAN MANAJEMEN SEBAGAI TEMPAT KULIAH DI PERGURUAN TINGGI - M. Azizul Khakim (Journal MISSY (Management and Business Strategy), 2022)
The purpose of this study was to examine the influence of culture, social, personal and psychological either partially or simultaneously on the selection of management majors. This research is a descriptive analysis research. The data in this study are primary data obtained through survey questionnaires sent to 50 respondents, while those that can be used in this analysis are 45 respondents or about 90.9%. In this research, validity test, reliability test and classical assumption test were conducted. Subsequently, the hypothesis was tested partially or simultaneously by using a significance probability number <0.05. Partial test results show that culture, personal and psychological have no effect on the selection of management majors, while social influences on the selection of management majors. Simultaneous test results show management. Simultaneous test results show that cultural, social, personal and psychological influence on the selection of management majors with an influence of 57%. Keywords: Culture, Social, Personal, Management Department